Kad ‘Kat Mana Tu?’ / Anis Hadirah Sulaiman, Hafiz Arif Sulaiman and Rosidah Misran - Sulaiman, Anis Hadirah; Sulaiman, Hafiz Arif; Misran, Rosidah (Faculty of Computer and Mathematical Sciences, 2023)
The mastery of mathematics is crucial for school students. However, there are misunderstandings in comprehending the coordinate topic in the Year 4 mathematics subject by students. They may become confused and ultimately fail to answer the topic effectively. A special card, ‘Kat Mana Tu?' is designed to address this issue. The materials used in creating this card can reduce waste and promote recycling. The cost involved is affordable and can be easily accessible to all students, making it user-friendly. Collaboration has been carried out to enhance the effectiveness of this product. Some modifications will be made, such as turning it into a bookmark and adjusting features in the card to make it usable for all sections in coordinate problems.